A Preservation from Oral and Practiced Rites of Passage in an African Tradition: Towards a Search for Identity in a Changing World in the Written - Kwakye-Nuako, Kwasi (Journal of black religious thought, 2023)
This is an originally observed rites of passages in a traditional African context. Through empirical observation and cultural anthropological esoteric engagement, traditions that have been traditionally preserved and kept in the oral or memory have been preserved in the written for the first time. An overview of the Sub-Saharan African context is followed by birthing and naming of the Meru peoples of Kenya. Additional traditions of rites for Meru boys, education, and integration lead to the conclusion.